2016
DOI: 10.18632/oncotarget.10313
|View full text |Cite
|
Sign up to set email alerts
|

Combined genetic and epigenetic interferences with interferon signaling expose prostate cancer cells to viral infection

Abstract: Interferons (IFNs) induce anti-viral programs, regulate immune responses, and exert anti-proliferative effects. To escape anti-tumorigenic effects of IFNs, malignant cells attenuate JAK/STAT signaling and expression of IFN stimulated genes (ISGs). Such attenuation may enhance the susceptibility of tumor cells to oncolytic virotherapy. Here we studied genetic and epigenetic mechanisms of interference with JAK/STAT signaling and their contribution to susceptibility of prostate cancer cells to viral infection. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 90 publications
2
40
0
Order By: Relevance
“…The authors showed that treatment with both decitabine and trichostatin (TSA) restored JAK1 levels, which proved to be necessary for IFN cascade to occur. Danziger et al [147] further elaborated on this; they showed that the same epigenetic modifiers partially restored IFN signaling but, very relevantly, they also showed that this attenuated, but did not completely block viral infection in PCa cells. Given the known antitumor effect, the authors then conclude that these epigenetic drugs may be considered for combination with therapeutic viruses, since infection of cells is still possible.…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 96%
See 1 more Smart Citation
“…The authors showed that treatment with both decitabine and trichostatin (TSA) restored JAK1 levels, which proved to be necessary for IFN cascade to occur. Danziger et al [147] further elaborated on this; they showed that the same epigenetic modifiers partially restored IFN signaling but, very relevantly, they also showed that this attenuated, but did not completely block viral infection in PCa cells. Given the known antitumor effect, the authors then conclude that these epigenetic drugs may be considered for combination with therapeutic viruses, since infection of cells is still possible.…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 96%
“…A summary of most recent studies addressing combination strategies between epigenetics and immune environment in PCa is depicted in Table 3 [108,[141][142][143][144][145][146][147][148][149][150][151][152]. Some studies have focused on epigenetic regulation of response to IFN, where both methylation and acetylation can be involved, as demonstrated by Dunn and collaborators [141].…”
Section: Role Of Immunoepigenetics?mentioning
confidence: 99%
“…Importantly, this mechanism has been targeted in oncolytic virotherapy for cancer. Cancer cells that have low PKR expression are sensitive to oncolytic viruses [78][79][80] . Our study showed that ILF3 mediates the RNA editing-dependent regulation of PKR expression, suggesting that these two factors are intertwined in gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In conjuncture with an inflammatory microenvironment, these molecular aberrations alter the activation state and function of a plethora of signal transduction pathways, including the JAK—signal transducer and signal transducer and activator of transcription (STAT) pathway ( 12 ). We and others have previously shown that a subset of PCa cells, and the LNCaP PCa cell line in particular, are defective in JAK1 expression ( 13 15 ). Notably, LNCaP cells express JAK2 and TYK2, but not JAK3, suggesting that multiple cytokine stimuli can be differently interpreted by these cells due to their expression pattern of JAK ( 16 ).…”
Section: Introductionmentioning
confidence: 98%
“…Notably, LNCaP cells express JAK2 and TYK2, but not JAK3, suggesting that multiple cytokine stimuli can be differently interpreted by these cells due to their expression pattern of JAK ( 16 ). Importantly, we have demonstrated that lack of JAK1 expression is associated with interferon-insensitivity and with hypersusceptibility of these cells to viral infections ( 15 ). In addition to interferon signaling, JAK1 mediates signaling by families of receptors that share the γc or gp130 subunits.…”
Section: Introductionmentioning
confidence: 99%